Prevalence of multidrug-resistant enteropathogenic Escherichia coli (EPEC) in river Gomti at Jaunpur city - Siya Ram; Roshan Lal Gautam; Shweta Singh; Devendra Singh; Ram Naraian; Nahida Arif (Cleaner Water)
The present study investigated the microbial EPEC load exhibiting three distinct marker genes: eaeA, bfp, and stx1 in the river Gomati water across Jaunpur City, India. In order to determine the prevalence of EPEC virulent strains that are multidrug-resistant, eight different public gathering sites on the river were selected from upstream to downstream flow. The highest population of total coliform (5400×103) and fecal coliforms (3500×107) were subsequently recorded from site #5 (Gopi ghat). A total of 46 EPEC strains were virulent, exhibiting eaeA and bfp genes, while none of them harbored the stx1 gene. All 46 strains contained the eaeA gene (100 %); however, only 11 isolates, as 24.10 %, exhibited bfp virulent genes. Most of the EPEC isolates from all seasons were resistant to more than three different classes of variable drugs and confirmed multidrug resistance. The highest 95.7 % of total isolates (44) exhibited resistance against tetracycline, while the lowest four isolates (8.6 %) against ciprofloxacin. Furthermore, it was evident that the bacterial population load and a load of virulent genes were found to be higher in the samples of the city's significant sites. This confirms the large-scale fecal contamination of water either through nearby animals or anthropogenic activities, which are needed to make proper management.